Aperfeiçoamento da regulamentaç\~ao de produtos e de investimentos privados em infraestrutura no Brasil - Marcelo Resende Allain (Instituto de Pesquisa Econômica Aplicada (IPEA), 2019)
– The present study examines which changes in financial instruments are recommended or have been made since then to enable expansion of investments with greater private sector participation in project financing. Such changes may be in the legislation of infrastructure debentures, the taxation of fixed income instruments, the CVM rules for investment funds or the project co-financing market practices.
Keywords: G28; H54; O16; 330; infrastructure; financial regulation; long term finance